Beberapa Aspek Epistemologi al-Shaykh Zayn al-’Abidin B. Muhammad al-Fatani: Suatu Penelitian Awal Terhadap Karyanya ’Aqidah al-Najin fi `Ilm Usul al-Din - Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2001)
The status and the significance of Muslim Malay scholars of the past and their works had been questioned by modern Malay mind. The place of this heritage and its significance is rarely realized. Consequently, there are accusations made on those scholars and the works were not properly evaluated. This article attempts to elaborate some aspects of epistemological concepts of al-Shaykh Zayn al’Abidin based on his work ’Aqidah al-Najin fi ’Ilm Usul al-Din. This elaboration is hopefully will give explanations on how the modern mind should deals with their heritage and how we can benefit from our scholars of the past.